2022
DOI: 10.1177/10892532221088216
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Thromboelastometry Values After On-Pump Cardiac Surgery – A Retrospective Cohort Study

Abstract: Background Viscoelastic coagulation monitoring is recommended for coagulation management after cardiac surgery, but optimum target values are poorly defined. Aims To determine “to-be-expected” values in rotational thromboelastometry (ROTEM) after heparin reversal, to correlate ROTEM parameters with fibrinogen levels and platelet count, and to estimate the effect of hemoglobin levels on these measurements. Methods We retrospectively analyzed 571 consecutive adult patients undergoing cardiac surgery with cardiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…MA HKH showed a strong relationship with fibrinogen concentration and platelet count, although K and angle showed moderate relationships with them. These results indicate that the predictive ability of TEG6s Platelet Mapping for conventional coagulation tests is comparable to that of rotational thromboelastometry (ROTEM; TEM Innovations Gmbh, Munich, Germany), which is another popular POC monitoring [ 23 - 25 ]. Furthermore, our study showed that K, angle, and MA HKH could predict the combination of fibrinogen > 150 mg/dL and platelet count > 100,000/µL with clinically acceptable accuracy.…”
Section: Discussionmentioning
confidence: 85%
“…MA HKH showed a strong relationship with fibrinogen concentration and platelet count, although K and angle showed moderate relationships with them. These results indicate that the predictive ability of TEG6s Platelet Mapping for conventional coagulation tests is comparable to that of rotational thromboelastometry (ROTEM; TEM Innovations Gmbh, Munich, Germany), which is another popular POC monitoring [ 23 - 25 ]. Furthermore, our study showed that K, angle, and MA HKH could predict the combination of fibrinogen > 150 mg/dL and platelet count > 100,000/µL with clinically acceptable accuracy.…”
Section: Discussionmentioning
confidence: 85%
“…Gauger et al hereby study the ROTEM POC testing for accuracy of "to-be-expected" values after cardiac surgery. 18 They demonstrate that ROTEM accurately estimates the fibrinogen level and platelet count. While this is not entirely novel, it does add value as scientific evidence specifically relevant to cardiac surgery and not merely in healthy volunteers.…”
mentioning
confidence: 98%